Visualization tools for the environmental component in the context of graphic design - Chernaia Z. I. (History of culture, study of art and philology: modern points of view, 2021)
The article is devoted to the problem of the ecological direction in modern graphic design. The issues of attention and attitude of man to the environment, their harmonization, the result of which is the preservation of natural balance; defining several means of visual interpretation of the ecological component and bionic.
Keywords: визуализация; экологическая культура; графический дизайн; visualization; ecological culture; экологический дизайн; экологический компонент; дизайн-продукт; бионическая стилизация; graphic design; ecological design; ecological component; design product; bionic stylization